Intake of stimulant foods is associated with development of parasomnias in children - Fabiana Ruotolo; Lucila B. F. Prado; Vanessa R. Ferreira; Gilmar F. Prado; Luciane B. C. Carvalho (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To verify if nighttime feeding habits can influence parasomnia in children. Method Seven private and four public Elementary Schools took part in the study. A total of 595 Sleep Disturbance Scale for Children were distributed to the parents of children aged from 7 to 8 years. Data of dietary recall, starting time to school, physical activity, and nutritional status were studied. Results Of the 226 questionnaires completed, 92 (41%) reported parasomnia. Girls had 2.3 times more the chance to parasomnia than boys. Children who consumed stimulant foods had 2.6 times more chance to have parasomnia than those of children who consumed non-stimulant foods. There were no difference between parasomnia and no-parasomnia groups in food type (p = 0.78) or timing of last meal before bedtime (p = 0.50). Conclusion Our findings suggest that intake of stimulant foods is associated with development of parasomnia in children.